2017
DOI: 10.18805/ijar.v0iof.7256
|View full text |Cite
|
Sign up to set email alerts
|

Determination of morphological and linear udder traits in Morkaraman, Tuj and Awassi sheep

Abstract: In this study, it was aimed that determination of udder measurements of Morkaraman, Tuj and Awassi ewes and the correlation between the results. Udder depth and width of the Awassi was higher than other breeds and respectively 13.09±0.32 cm, 14.07±0.43 cm. In Morkaraman, teats length (2.65±0.06 cm) and diameter of the teats (1.83±0.06 cm) were higher from other breeds. The important statistical difference was found between breeds for udder depth (P less than 0.05), very important statistical difference was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…Measurements related to udder size (UW, UC, UL and UD) were positively and significantly correlated. Similar to the findings of this study, positive and significant correlations were reported between udder measurements in different breeds of sheep (Özyurek et al 2018;Shettima et al 2022). From the teat measurements, TD showed negative correlations with UW (-0.381, P <0.01) and DBT (-0.426, P<0.01) and positive (0.628, P<0.0001) correlations with TL.…”
Section: Correlations Among Udder Traitssupporting
confidence: 91%
“…Measurements related to udder size (UW, UC, UL and UD) were positively and significantly correlated. Similar to the findings of this study, positive and significant correlations were reported between udder measurements in different breeds of sheep (Özyurek et al 2018;Shettima et al 2022). From the teat measurements, TD showed negative correlations with UW (-0.381, P <0.01) and DBT (-0.426, P<0.01) and positive (0.628, P<0.0001) correlations with TL.…”
Section: Correlations Among Udder Traitssupporting
confidence: 91%
“…The mean udder circumference was 34.47±0.8 and 37.61±0.9 cm for Morkaraman and Awassi, respectively. In a different study conducted by Ozyurek et al (2018), the udder circumference was 36.08±0.58 for Morkaraman and 35.32±0.97 for Awassi. Udder circumference and udder length were found to be higher in the Awassi while right and left udder lengths were found to be longer in Morkaraman.…”
Section: Resultsmentioning
confidence: 88%
“…Anket uygulanan işletmelerin büyük bir kısmında (%86), hayvan başına ortalama günlük süt veriminin 0,5 litre olduğu tespit edilmiştir. Farklı araştırmacılar tarafından çalışmadakine benzer sonuçlar (8,16) belirtilirken; çalışmadaki ortalama değerlerden daha düşük bildirişler de bulunmaktadır (19,21).…”
Section: Discussionunclassified
“…Çalışmadaki işletmelerin %99'u herhangi bir birliğe üyedir. Söz konusu durumla paralellik gösterecek şekilde, Erzincan ili koyunculuk işletmelerinde(16) ve Burdur ilinde koyun ve keçi işletmeleri üzerinde yapılan çalışmada (8) üyelik oranı oldukça yüksek bulunmuştur. İlaveten Taşkın ve ark (17).…”
unclassified